Marikana : a Report from South Africa. - Shenker, Jack (Zed Books, 2015)
On 16 August 2012, the world looked on in horror as South African police gunned down striking mine workers at Marikana, leaving thirty-four dead and many more wounded. It was a massacre that echoed apartheid-era violence at Sharpeville and Soweto, shattering the international image of South Africa as a liberated 'rainbow nation'. The bloodshed laid bare the lingering inequalities and class tensions that have endured beyond South Africa's democratic transition, and which the ruling African National Congress has done little to address. Marikana, an ebook exclusive by award-winning Guardian jour.